The Role of the Eukaryotic Translation Initiation Factor 4E (eIF4E) in Neuropsychiatric Disorders - Amorim, Inês S.; Lach, Gilliard; Gkogkas, Christos G. (Frontiers in Genetics, 2018)
Protein synthesis in eukaryotic cells is a complex, multi-step and tightly regulated process. Translation initiation, the rate limiting step in protein synthesis, is dependent on the activity of eukaryotic translation Initiation Factor 4E (eIF4E). eIF4E is the cap-binding protein which, in synergy with proteins such as the helicase eIF4A and the scaffolding protein eIF4G, binds to mRNA, allowing the recruitment of ribosomes and translation initiation. The function of eIF4E is tightly regulated in cells under normal physiological conditions and can be controlled by post-translational modifications, such as phosphorylation, and by the binding of inhibitory proteins, including eIF4E binding proteins (4E-BPs) and CYFIP1. Recent studies have highlighted the importance of eIF4E in normal or aberrant function of the nervous system. In this mini-review, we will highlight the role of eIF4E function and regulation in the pathophysiology of neurodevelopmental and neuropsychiatric disorders.